2022
DOI: 10.1021/acs.langmuir.1c03106
|View full text |Cite
|
Sign up to set email alerts
|

Revisit the Hydrated Cation−π Interaction at the Interface: A New View of Dynamics and Statistics

Abstract: Carbon-based matter, such as biomolecules and graphitic structures, often form a liquid–solid/soft matter interface in salt solution and continuously affect the surrounding cations through hydrated cation−π interactions. In this Perspective, we revisit the effect of the hydrated cation−π interactions at the interface using statistical physics, which reveals how hydrated cation−π interactions affect every component dynamically and cause a time-dependent statistical effect at the liquid–solid/soft interface. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…As shown in Figure 5b, there appear peaks at 84.24 (4f7/2) and As shown in Figure 5a, several Bragg peaks appeared at various diffraction angles (2θ). The peak at ~24 • is from the rGO membranes [26], and the peaks at ~38.1 • , 44.4 • , 64.5 • and 77.5 • are close to the value of 2θ for the (111), ( 200), ( 220) and (311) surface of gold, respectively. To further verify the chemical state of Au 3+ ions on the membranes, we performed an XPS experiment.…”
Section: Characterizationmentioning
confidence: 55%
“…As shown in Figure 5b, there appear peaks at 84.24 (4f7/2) and As shown in Figure 5a, several Bragg peaks appeared at various diffraction angles (2θ). The peak at ~24 • is from the rGO membranes [26], and the peaks at ~38.1 • , 44.4 • , 64.5 • and 77.5 • are close to the value of 2θ for the (111), ( 200), ( 220) and (311) surface of gold, respectively. To further verify the chemical state of Au 3+ ions on the membranes, we performed an XPS experiment.…”
Section: Characterizationmentioning
confidence: 55%
“…As reviewed recently by Jin et al [5], Zhang et al [6], and Geim [7], 2D Å-scale channels have become the attractive platforms for investigating mass transport under Å-scale confinement. Recently, graphenebased laminar membranes or devices composed of 2D Å-scale or nm-scale ion channels [8][9][10][11][12][13][14][15][16][17][18][19][20][21] have also become attractive platforms to mimic natural ion channels because they can provide not only ion dehydration effects [8,13,[15][16][17] but also cation-π interaction [18][19][20][21], as involved in biological ion channels [1,2,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although Bansal et al found that large particles (~0.9 μm in diameter) were uniformly distributed, while small particles formed a ring on hydrophobic substrates with the contact angle >95° (i.e., polydimethylsiloxane and gas diffusion layer) [ 39 ], most researches indicate that this CRE-based separation method can only apply to suspensions with very low specimen fractions (<0.04 vol.%) [ 32 , 33 ] on sufficiently hydrophilic substrates [ 32 , 33 , 34 , 35 , 36 ]. Our previous work demonstrated that the CRE can be effectively controlled by simply adding trace amounts of salt to colloid suspensions [ 40 , 41 ]. It can be contributed to the enhanced adsorption between the particles and the aromatic substrate through strong hydrated cation-π interactions [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%